Tracking gender-based violence and backlash against women’s rights in the digital space: Cases from Bangladesh - Mahpara, Pragyna; Antara, Iffat Jahan; Nath, Shravasti Roy; Pabony, Nuha Annoor (BIGD, 2024)
Social media platforms such as Facebook can be effective in spreading positive awareness of gender equality and women’s rights; however, those who oppose these beliefs also use the same platform as a medium for spreading their ideologies. This paper aimed to examine the backlash faced by women public figures who are active on social media and shared content about Gender-based violence, along with the actors behind it. The study also looked into two controversial national events which raised discussions on sexual harassment and violence against women and the effectiveness of the Digital Security Act (DSA) 2018 and other relevant laws and policies used to counter these sorts of violence. A qualitative approach was followed with an analysis of the Facebook accounts related to the case studies and some quantitative data was collected through CrowdTangle software. The study showed that all female public figures faced a backlash mostly from men and boys with some comments from women. While they sought a remedy, DSA did not play a strong role. Women’s rights issues such as women’s education, employment, and domestic violence are seen as liberal feminism while issues like consent, divorce, single parenthood, sexuality, and gender diversity are considered more radical issues.